Non-suicidal Self-Injury in Clinical Practice - Hauber, Kirsten; Boon, Albert; Vermeiren, Robert (Frontiers in Psychology, 2019)
Background: Non-suicidal self-injury (NSSI) among adolescents is a major public health concern and a common problem in clinical practice. The aim of this study was to examine different aspects of NSSI in a high-risk adolescent sample in clinical practice in association with personality disorders, symptoms, and coping skills to enhance the understanding of NSSI and improve treatment interventions. Method: In a sample of 140 adolescent inpatients treated for personality disorders, assessments were performed pre-treatment and post-treatment using a questionnaire on NSSI developed for clinical practice, the Structured Clinical Interview for DSM personality disorders, the Symptom Check List 90, and the Cognitive Emotion Regulation Questionnaire. Results: NSSI was common (66.4%) among the inpatient adolescents. Of those without NSSI behaviour (n = 47), 10 (21.3%) started NSSI during treatment. NSSI was related to number of personality disorders and not to one specific.. Participants who experienced NSSI (n = 93) reported significantly more symptoms and the negative coping strategy self-blame. They scored lower on the positive coping strategies of refocusing and reappraisal. Conclusion: NSSI in adolescent clinical practice is common, not exclusive to borderline personality disorder and could be contagious. Reducing self-blame and enhancing positive refocusing and positive reappraisal seem important treatment targets.